Early Outcomes of Thoracofemoral Bypass for Aortoiliac Occlusive Disease: A 10-Year Single-Center Experience - Sharma, Anil; Dixit, Sunil; Sharma, Mohit; Mittal, Sourabh; Shah, Apurva; Goyal, Shefali (AORTA, 2025)
Thoracofemoral bypass is primarily utilized as a secondary intervention for juxtarenal aortoiliac occlusive disease, with limited instances of its application as an initial treatment, leading to uncertain long-term outcomes. This analysis aims to scrutinize the 10-year experience and early outcomes of 90 patients who underwent thoracofemoral bypass as a primary procedure.A retrospective analysis was conducted on patients undergoing thoracofemoral bypass for severe aortoiliac occlusive disease between August 2012 and August 2022. The primary indication was complete abdominal aorta obstruction at the renal artery level with an unsuitable site for aorta clamping. The BARD IMPRA expanded polytetrafluoroethylene vascular graft was employed for thoracobifemoral bypass surgery.Among the 90 patients, 83 (92.22%) were male, and 7 (7.78%) were female, with ages ranging from 51 to 77 years. Intraoperative and postoperative data were analyzed, and the mean follow-up duration was 30 days. The 30-day mortality rate was 3.33% (n = 3). Major morbidities included graft occlusion in one patient, managed by embolectomy, and ascites in another patient, addressed conservatively.This study demonstrates that thoracic aorta to femoral artery bypass, as a simple extra-anatomic bypass technique, can yield favorable outcomes when chosen as the initial treatment for patients with juxtarenal total aortoiliac occlusive disease. Thoracofemoral bypass exhibits a safe, acceptable outcome with reliable patency.
Keywords: atherosclerosis; peripheral vascular disease; thoracobifemoral bypass